Literature and revolution in modern China : Lu Xun, Leon Trotsky, and Chen Duxiu - Yuzo, Nagahori; Benton, Gregor (2025)
"This book reconstructs Lu Xun's literary theory and political position within its historical context, considering Trotsky's literary theory and his relationship with the Chinese Trotskyists and the Chinese Communist Party. It also corrects errors and shortcomings in conventional studies of Lu Xun. At the same time, it aims to show how Lu Xun was used by the Chinese Communists and Mao Zedong for political purposes, beginning in the Yan'an years and culminating during the Cultural Revolution. Additionally, it seeks to rescue Lu Xun from the distortion of his legacy by the Chinese Communist literary establishment, Mao Zedong, and Stalinism"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Lu, Xun, -- 1881-1936 -- Criticism and interpretation; Lu, Xun, -- 1881-1936 -- Political and social views; Communism and literature -- China; China -- History -- Cultural Revolution, 1966-1976; Literary criticism